Pengaruh Transparansi Dan Akuntabilitas Terhadap Kepercayaan Anggota Pada Koperasi Karyawan XXX Di Kabupaten Tabalong - Alhamdi Rasyid; Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This study aims to analyze the effect of transparency and accountability on the trust of members in an employee cooperative. The research was conducted using a quantitative survey method. Data were collected through questionnaires distributed to 88 respondents and analyzed using validity tests, reliability tests, and multiple linear regression analysis. The study also included classical assumption tests such as normality, multicollinearity, and heteroskedasticity tests. The results indicate that the transparency variable (X1) has a positive but insignificant effect on member trust (Y). Similarly, the accountability variable (X2) also shows a positive but insignificant effect on member trust (Y) partially. Simultaneously, transparency (X1) and accountability (X2) do not have a significant effect on member trust (Y). However, members generally gave positive evaluations of cooperative management, particularly in terms of transparent information delivery and accountable reporting. The analysis results demonstrate that transparency and accountability significantly influence member trust in the cooperative, contributing 75.9% to variations in member trust (R² = 0.759). Partially, the transparency variable has a more dominant influence compared to accountability, with standardized coefficient values of 0.606 and 0.294, respectively. Validity and reliability tests show that all research instruments meet high validity and reliability standards